A Deep Learning Based Accident Detection System - S.Lalitha, Chandra Ananya, Gudesi Bhanusha, Yenuguwar Anjali (Journal of Computational Analysis and Applications (JoCAAA), 2024)
In this fast-paced world, the number of deaths due to accident is growing at an expeditious rate. Majorreasons for these accidents are rash driving, drowsiness, drunken driving, carelessness, etc. An indicator ofsurvival rates after detecting accidents is the time between the occurrence of accidents